Preparation of Functionalized Hybrid Membranes Cured at Different Temperatures and Their Adsorptions for Lead(II) - Liu, Junsheng; Wu, Linlin; Chen, Xinghua (Asian Journal of Chemistry, 2015)
A series of functionalized hybrid membranes cured at different temperatures were synthesized via sol-gel process, in which the -NH2 groups were grafted on the molecular chains by the functionalization of Si-OH groups in silicone with the -OH groups in the PVA chains. FTIR spectra confirmed the existence of functionalized groups in the molecular chains. Thermogravimetric analysis and DSC revealed that the thermal stability of these hybrid membranes could arrive at 240 °C and their degradation temperatures were located within the temperature range of 220-275 °C. Adsorption experiments demonstrated that these hybrid membranes could be used to adsorb lead(II) from water, indicating promising applications in wastewater treatment. Meanwhile, it was confirmed that the curing temperature had some effects on lead(II) adsorption on these hybrid membranes. Moreover, it was found that lead(II) adsorption on these hybrid membranes increased not only with an increase in the initial concentration of solution, but also increased with the elevated solution temperature. The upward trend in lead(II) adsorption capacity with the increasing solution temperature reveals that lead(II) adsorption on these hybrid membranes was a spontaneous process. These findings are very meaningful in the removal of lead(II) from lead(II) containing water using these functionalized hybrid membrane as efficient adsorbents.